2014
DOI: 10.1007/s12013-014-9956-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Comparing Ultrasound-Guided Procedure with the Seldinger’s Technique for Placement of Implantable Venous Ports

Abstract: The aim of this randomized controlled study was to compare ultrasound-guided procedure with the Seldinger's technique for placement of implantable venous ports. A total of 214 patients were randomized to receive TIAP placement by either ultrasound-guided procedure or the Seldinger's technique. Complications and pain perception were compared between these two groups. No severe perioperative or periinterventional complication occurred. Significantly (P < 0.05) lower pain perception was observed in the ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Seven studies [ 15 , 17 , 18 , 23 , 31 , 38 , 41 ] that reported on catheter dislocation in 2463 patients showed a significant difference favoring the IJV group (1.08 % in the IJV group and 2.54 % in the SCV group; OR 0.43, 95 % CI 0.22–0.84; P = 0.013) (Fig. 3b ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies [ 15 , 17 , 18 , 23 , 31 , 38 , 41 ] that reported on catheter dislocation in 2463 patients showed a significant difference favoring the IJV group (1.08 % in the IJV group and 2.54 % in the SCV group; OR 0.43, 95 % CI 0.22–0.84; P = 0.013) (Fig. 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…Agreement on study selection between the two reviewers was high (k = 0.94). Among the included studies, there were three RCTs [ 16 , 39 , 41 ] and two prospective non-randomized controlled trials [ 15 , 31 ]. The remaining seven studies [ 17 , 18 , 21 , 23 , 38 , 40 , 42 ] were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more pH‐sensitive materials and techniques have been developed for pH sensing . In these, optical methods have received particular attention owing to highly sensitive, noninvasive, disposable, easily miniaturized and high throughput properties .…”
Section: Introductionmentioning
confidence: 99%